2015
DOI: 10.1002/btpr.2193
|View full text |Cite
|
Sign up to set email alerts
|

At-line process analytical technology (PAT) for more efficient scale up of biopharmaceutical microfiltration unit operations

Abstract: Tangential flow microfiltration (MF) is a cost-effective and robust bioprocess separation technique, but successful full scale implementation is hindered by the empirical, trial-and-error nature of scale-up. We present an integrated approach leveraging at-line process analytical technology (PAT) and mass balance based modeling to de-risk MF scale-up. Chromatography-based PAT was employed to improve the consistency of an MF step that had been a bottleneck in the process used to manufacture a therapeutic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…On‐line process analytical technology (PAT) would also need to be incorporated as part of any commercial continuous process. Watson et al recently showed how at line PAT could be incorporated in the scale up of a microfiltration unit; a similar approach could potentially be used to incorporate PAT in a CCTC system.…”
Section: Discussionmentioning
confidence: 99%
“…On‐line process analytical technology (PAT) would also need to be incorporated as part of any commercial continuous process. Watson et al recently showed how at line PAT could be incorporated in the scale up of a microfiltration unit; a similar approach could potentially be used to incorporate PAT in a CCTC system.…”
Section: Discussionmentioning
confidence: 99%
“…Small production skids, disposable units, variable raw materials, and lack of real-time online measurement devices are challenges for PAT integration, but new, sophisticated instruments show promising improvements [82] . Product attribute control is now possible within the bioreactor, for example with MAST (Modular Automated Sampling Technology), and advances in Raman spectroscopy, at-line surface plasmon resonance (SPR), SU sensors, chemometric methods, and ultra high performance liquid chromatography (UPLC) at line monitoring are helping manufacturers overcome hurdles in DSP PAT integration [83] , [83] , [84] , [85] , [86] , [87] , [88] .…”
Section: Summary and Outlooksmentioning
confidence: 99%
“…It was used to measure both protein concentration and purity across the entire process, including excluded chromatographic fractions. The method utilized a 2.1 × 150 mm column (Waters Acquity BEH Shield C18 1.7 µm, Catalog #186003376) and a gradient of 27%–33% acetonitrile over 28 min employing a water/acetonitrile/trifluoroacetic acid gradients at a flow rate of 0.2 mL min −1 on a Waters H‐Class UPLC instrument (Watson et al, 2016). Additionally, this same method was used to measure purity at release, further enabling an integrated control strategy across the entire process assuring the purity target was met at the final drug substance (DS).…”
Section: Introduction Key Elements and Themesmentioning
confidence: 99%